The live sheep export supply chain: when operational and societal complexities collide - Jackson, Elizabeth; Adamson, D. (2018)
This paper takes a supply chain perspective on the business systems involved in the trade of live sheep from Australia to the Middle East. Live export supply chains are complex as they must encompass efficiency, maintenance of quality and adhere to international animal welfare protocols. This paper explores the consequences resulting from business systems' failure, based on a case study from 2012 when protocols in the international trade of live sheep were compromised. Key themes to emerge from the case study relate to supply chain control and resilience, the moral obligations of governments to manage societal exposure to unsafe food and the management of unscrupulous operators in the food supply chain. The originality of this work lies in its consideration of 'live cargo' and the challenges of unforeseen circumstances in managing the physical distribution of live animals transported by sea.